Durkheimian sociology cultural studies - Alexander, Jeffrey C. 1947- (Cambridge University Press, 1988)
The classic works of Emile Durkheim are characterized by a structural approach to the understanding of collective behaviour, and it is this element of his writings that has been most taken up by modern social science. This volume, however, rejects the dominant structural approach, and draws instead on Durkheim's later work, in which he shifted to a symbolic theory of modern industrial societies that emphasized the importance of ritual and placed the tension between the sacred and the profane at the center of society. In so doing, the contributors offer both a radically different approach to Durkheimian sociology and a new way of linking the interpretation of culture and the interpretation of society. In his introduction to the volume, Jeffrey Alexander elaborates the new interpretation of Durkheim that informs the contributions. His arguments form a background for the lively and provacative chapters that follow, which provide broadly cultural interpretations of such topics as popular upheavals and social movements, ranging from the French Revolution to the massive rebellions in Poland and Nicaragua in the 1980s; political crisis, from Watergate to the crisis of legitimation in contemporary capitalism; and the creative and contingent element in symbolic behaviour, including the symbolics of intimate friendship, and the ritual and rhetoric of media events. In addition to re-examining Durkheimian sociology, the essays also demolish the myth that attention to cultural values implies conservatism or the inability to analyze social change, and challenge the common antithesis between normative theory and microsociology. Its exploration of the links between Durkheimian sociology and the most important developments in contemporary sociology, history, anthropology and semiotics will ensure it a broad appeal across the social sciences